Peran Istri Nelayan Dalam Meningkatan Perekonomian Keluarga Di Kampung Laut, Tanjung Jabung Timur - subhan muhammad; Hardi Nofriansyah Saputra; A Tarmizi (ILTIZAM Journal of Shariah Economics Research, 2022)
This study aims to determine the role of the wife in improving the family economy, the form of the role or participation of the wife in helping to increase household income and the impact of the wife's dual role in improving the family economy. This research uses a descriptive qualitative approach. In this study using data analysis techniques such as data reduction, data collection, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the driving factors or the background of the wife play a role in increasing the family economy, namely the husband's income is insufficient and the high cost of living. The wife's involvement in improving the family's economy is to provide opportunities for wives or housewives in the form of trading knowledge they have, skills they have and the ability to work in other places. The impacts include positive and negative impacts, the positive impacts can help increase family income, can help improve status in the family and build a sense of mutual understanding between family members. The negative impact is the social impact that is felt by the children, the attention and affection from their mother will decrease, and attention in terms of education is also greatly reduced because both parents work together.